The Potential of Interactive Teaching Materials of Natural Science Practicum Courses in Elementary School by Distance Learning - Budiastra, A.A. Ketut; Ichwan, Ichwan; Kadarisman, Kadarisman; Casmat, Memet; Erlina, Nia (Universitas Pahlawan Tuanku Tambusai, 2022)
Distance learning is not new to education, but it requires more dedication and initiative than the implementation of conventional education. Distance learning in lectures is the implementation of learning when students and lecturers cannot attend face to face at the same time in the campus lecture hall. One of the efforts to implement distance learning is to use interactive literacy activities. This study aims to examine that this era has implications for Indonesia as a country that wants to become a developed country, especially in education. This type of research is descriptive research in the literature. The results of the description discuss (1) Efforts to adapt natural science practicum learning according to the times; (2) Provision of teaching materials to support the tutorial interaction process in natural science practicum activities; and (3) Students' readiness in implementing natural science practicum in distance learning. This study highlights several theoretical and empirical contributions. It provides recommendations that the implementation of remote practicum through digital media and the use of materials available in the surrounding environment need interactive instruction support to support student practicum competencies